Predicting the therapeutic response to cognitive behavioural therapy in patients with pharmacoresistant obsessive-compulsive disorder - Prasko, Jan; Raszka, Michal; Adamcova, Katarina; Grambal, Ales; Koprivova, Jana; Kudrnovská, Hana; Latalova, Klara; Vyskocilová, Jana (Neuro endocrinology letters, 2009)
OBJECTIVE: The aim of our study was to establish the efficacy of CBT on the sample of non-selected medication-resistant patients with OCD and to search for predictors of therapeutic response in such a group. METHODS: The treatment was carried out under usual conditions at the department for anxiety disorders. Systematic CBT steps were tailored to the needs of each patient. Pharmacology treatment remained grossly unchanged during the trial period. We used the following outcome measures in the study: Yale-Brown Obsessive Compulsive Scale, subjective version (S-Y-BOCS), the Clinical Global Impression - Severity of Illness scale (CGI-S), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Somatoform Dissociation Questionnaire (SDQ-20) and Dissociative Experience Scale (DES). The primary outcome measure was a decrease by 35% in Y-BOCS rating. Remission was defined as a 12 point score or lower in Y-BOCS and 1 or 2 points in CGI-S. RESULTS: 47 patients completed the study (19 male and 28 female). One female patient refused to participate. All patients completed at least 5 weeks of intensive CBT programme and showed significant improvement on Y-BOCS, CGI-S, and BDI scales. At the end of the treatment 40.4% of the patients achieved clinical remission according to the CGI-S scale. The main characteristics present at the beginning of the trial increasing probability of achieving improvement or remission during the treatment were a Y-BOCS score lower than 22, good insight, higher resistance to symptoms, low level of dissociation, and aggressive obsessions. CONCLUSION: As negative predictors we identified higher scores in Y-BOCS, poorer insight, low resistance to symptoms, high level of dissociation, obsessions focused on control/symmetry and obsessive slowness/ambivalence as associated with poor improvement.
Keywords: léková rezistence; lidé; výsledek terapie; Adult; Obsessive-Compulsive Disorder; Female; průzkumy a dotazníky; Cognitive Behavioral Therapy; Humans; obsedantně kompulzivní porucha; kognitivně behaviorální terapie; mužské pohlaví; mladý dospělý; Drug Resistance; ženské pohlaví; Young Adult; Treatment Outcome; Male; dospělí; Surveys and Questionnaires